Supply Chain Analysis for Water and Sanitation Technology Research Project (Case Study in Morotai Island, North Maluku Province) - Dimas Hastama Nugraha; Rezeki Peranginangin Peranginangin; Erlita Pramitaningrum Pramitaningrum (Spektrum Industri, 2021)
Morotai’s sanitation and clean water technology is covering sanitation technology (bio filter, sanitary pond) and clean water (SPC, Reserve Osmose). This technology is ready to be applied in Daruba Pantai, Morotai, North Maluku and all of its technology originated from Java. Research problem’s focus on supply chain. Research objectives eager to see to what extent the supply chain of sanitation and clean water technology, from the technology producers which are mostly located in Java and the application location is in Morotai. The study of Supply Chain in Clean Water and Sanitation Technology Implementation using an applied based research approach. This study refers to scientific research and attempt to solve practical problems. The result of this study, any supply chain for four technologies in Morotai. The results consist of identifying supply chain components, determining network dimension structure that consists of three types dimension, determining type of business chain, and mapping supply chain. For the sanitation technology (bio filter), there are six certified bio filter suppliers and one of them will be selected as the supplier of the construction project in Morotai area. At the sanitary ponds technology, the constituent component/material can be retrieved from local suppliers in Morotai. For Simple Water Management Installation-Quick Sand Filter/SPC, the technology constituent component itself comprises of ground water tank, pump, roof tank, and Quick Sand Filter (made of fibre). This material is brought from the supplier named CV. Lusika in Bandung. Then, the RO technology constituent component is quite many comprising of water inlet valve, pre-filter, RO membrane, post-filter, automatic inspection valves, flow blockers, reservoir, faucet, and exhaust pipe. RO system unit is brought from the supplier called PT. Zeofilt Water Treatment that located in Bandung.